Prevalence and Antimicrobial Susceptibility Patterns of Neisseria gonorrhoeae among Suspected Patients Attending Private Clinics in Jimma, Ethiopia - Addisu Sahile; Lule Teshager; Minale Fekadie; Mulatu Gashaw (International Journal of Microbiology)
Background. In most African countries including Ethiopia, Neisseria gonorrhoeae infections were diagnosed clinically and its antibiotic susceptibility was rarely tested. This study aimed to determine the prevalence and antimicrobial susceptibility patterns of N. gonorrhoeae among suspected patients attending private clinics in Jimma, Ethiopia. Methods. Institution-based cross-sectional study was conducted to determine the prevalence and antimicrobial susceptibility pattern of N. gonorrhoeae isolated from urogenital specimens. Urogenital samples were collected aseptically and then transported using Amie’s transport media and processed in a microbiology laboratory following the standard protocol. Results. Of the total 315 samples examined, 31 (9.8%) were confirmed to have gonococcal infection. Of these, 30 (96.7%) were females. High proportion of culture confirmed cases (18 (12.5%)) were observed in the 20–24 age group. All of the identified organisms were susceptible to ceftriaxone and had high resistance to penicillin (80.6%) and tetracycline (54.8%). Conclusion. The prevalence of gonococcal infection is high. In the current study, participants who have no information about sexually transmitted infection were more likely to be infected by N. gonorrhoeae. According to our study, ciprofloxacin is effective against gonococcal infection.